2019
DOI: 10.1111/bpa.12768
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prognostic markers in diffuse midline gliomas H3K27M‐mutant

Abstract: Pediatric diffuse midline gliomas are devastating diseases. Among them, diffuse midline gliomas H3K27M-mutant are associated with worse prognosis. However, recent studies have highlighted significant differences in clinical behavior and biological alterations within this specific subgroup. In this context, simple markers are needed to refine the prognosis of diffuse midline gliomas H3K27M-mutant and guide the clinical management of patients. The aims of this study were (i) to describe the molecular, immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 42 publications
5
23
0
Order By: Relevance
“…Diffuse midline glioma (DMG), H3 K27M mutant (WHO grade IV) is listed as a separate CNS tumor entity since 2016 [5], after large sequencing efforts had discovered H3 K27M mutations frequently appearing in gliomas located in midline structures [11]. Over time, we and others have observed single cases of DMG with concomitant mutations within FGFR1 or BRAF [1,2,4,6,7,9,10,[12][13][14]. FGFR1 and BRAF mutations are typical hallmarks of low grade glioma, such as pilocytic astrocytoma, ganglioglioma, or dysembryoplastic neuroepithelial tumor [3,8].…”
mentioning
confidence: 99%
“…Diffuse midline glioma (DMG), H3 K27M mutant (WHO grade IV) is listed as a separate CNS tumor entity since 2016 [5], after large sequencing efforts had discovered H3 K27M mutations frequently appearing in gliomas located in midline structures [11]. Over time, we and others have observed single cases of DMG with concomitant mutations within FGFR1 or BRAF [1,2,4,6,7,9,10,[12][13][14]. FGFR1 and BRAF mutations are typical hallmarks of low grade glioma, such as pilocytic astrocytoma, ganglioglioma, or dysembryoplastic neuroepithelial tumor [3,8].…”
mentioning
confidence: 99%
“…Wu et al [16] reported that 78% of H3K27M mutations are detected in diffuse intrinsic pontine glioma, approximately 60% and 18% of which involve the H3F3A gene and HIST1H3B gene, respectively. Most recently, Dufour et al [61] studied 49 patients with paediatric diffuse midline glioma and discovered that 80% of the tumour carried H3K27M mutations, of which 63.6% and 15.9% of the H3F3A and HIST1H3B genes, respectively, were mutated. The studies demonstrated that H3F3A and HIST1H3B mutations are common in the pHGGs derived from midline locations of the brain.…”
Section: H3k27m Mutations As Biomarkers In Paediatric High-grade Gliomasmentioning
confidence: 99%
“…Paediatric groups that suffer from diffuse intrinsic pontine glioma containing H3K27M mutations have a worse prognosis with a median survival of 0.73 years, as compared to those harbouring wild-type tumours: 4.59 years [67]. Similarly, children with diffuse midline glioma also show poor prognosis, with a median overall survival (OS) of 0.78 years [61]. Generally, many studies concluded that pHGGs with H3K27M mutations are always associated with a worse prognosis.…”
Section: H3k27m Mutations As Biomarkers In Paediatric High-grade Gliomasmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to H3 K27M, ATRX, TP53, NF1, FGFR1, PDGFRA, PTPN11, and BRAF alterations have been found in various pediatric and adult midline glioma subtypes, while 1p/19q co-deletion were seldom reported (8,12,14,18,19). Many of these frequently observed genes are key members of PI3K/mTOR and RAS-MAPK pathways that could potentially provide novel therapeutic options for these otherwise devastating diseases (20)(21)(22)(23)(24). Nevertheless, the prognostic significance of genetic aberrations and oncogenic pathways was only weakly addressed for midline glioma with or without H3 K27M mutation (20) and comprehensive molecular characterization is still lacking.…”
Section: Introductionmentioning
confidence: 99%